Assessment of genetic structure among eastern North Pacific gray whales on their feeding grounds. Issue 4 (2nd April 2014) - Lang, Aimée R.; Calambokidis, John; Scordino, Jonathan; Pease, Victoria L.; Klimek, Amber; Burkanov, Vladimir N.; Gearin, Pat; Litovka, Dennis I.; Robertson, Kelly M.; Mate, Bruce R.; Jacobsen, Jeff K.; Taylor, Barbara L.
Abstract Although most eastern North Pacific (ENP) gray whales feed in the Bering, Beaufort, and Chukchi Seas during summer and fall, a small number of individuals, referred to as the Pacific Coast Feeding Group (PCFG), show intra‐ and interseasonal fidelity to feeding areas from northern California through southeastern Alaska. We used both mitochondrial DNA (mtDNA) and 12 microsatellite markers to assess whether stock structure exists among feeding grounds used by ENP gray whales. Significant mtDNA differentiation was found when samples representing the PCFG (n = 71) were compared with samples (n = 103) collected from animals feeding further north (FST = 0.012, P = 0.0045). No significant nuclear differences were detected. These results indicate that matrilineal fidelity plays a role in creating structure among feeding grounds but suggests that individuals from different feeding areas may interbreed. Haplotype diversities were similar between strata (hPCFG = 0.945, hNorthern = 0.952), which, in combination with the low level of mtDNA differentiation identified, suggested that some immigration into the PCFG could be occurring. These results are important in evaluating the management of ENP gray whales, especially in light of the Makah Tribe's proposal to resume whaling in an area of the Washington coast utilized by both PCFG and migrating whales.